SUATU STUDI LITERATUR: AKTIVITAS ANTIDIABETIC DARI KULIT JERUK (Citrus sp.) - Maya Sari Mutia; Chrismis Novalinda Ginting; OK Yulizal (Universitas Prima Indonesia, 2021)
Diabetes mellitus is a chronic metabolic disease, which is not able to secrete insulin in sufficient quantities or the body is unable to use insulin effectively so there is an excess glucose level and immediately suffer from some complications against the organs. Diabetes mellitus can be cured by herb utility which are thought to have compounds that has an antidiabetic effect. Therefore, this literature study discusses the antidiabetic activity of orange peel (Citrus sp.). The literature search was carried out on the Google Scholar search engine which used some keyword included antidiabetic, extract, orange peel, Citrus. In this literature study, there are inclusion and exclusion criteria for selecting journals as literature sources. The results of 12 literatures review that orange peel had antidiabetic activity by decrease blood glucose levels in some animal trials that had received an effective dose of orange peel extract in each of the reviewed studies. Hence, it can be concluded that various type of Citrus peels has antidiabetic effect.